Synthesis of Linear Array Antenna with Wide Range of beamwidths using DE Algorithm - Grandhi, Challaram; Grandhi, N.; Venkateswara Rao, N. (International Journal of Engineering and Technology, 2018)
In many communication systems like Radar and point to point micro links there is a need of both narrow and wide beams. In target applications Antennas with narrow beam width is required on the other hand, for spy application antennas with wider beam width are required. Generally, for linear array antennas the beams width will be narrowed by increase in the number of elements in the array. To obtain narrow beams without a significant increase in the number of radiation elements in the array, the optimization algorithms are used. By the use of optimization algorithms the wider beams can also be employed in reverse procedure of choosing the highest output for a given set of random inputs. These wide ranges of beam width are obtained without any increase in the side lobe levels that is, by maintaining the side lobe level below -20db. Random stochastic methods like Particle swarm optimization (PSO), Genetic algorithm (GA), Biogeography-based optimization (BBO) and Differential Evolution Algorithm (DE) are used and the results are compared.Â Â